2023
DOI: 10.1186/s40794-023-00202-z
|View full text |Cite
|
Sign up to set email alerts
|

Herpes zoster vaccine awareness and acceptance among adults in Saudi Arabia: a survey-based cross-sectional study

Sarah AlMuammar,
Afaf Albogmi,
Manar Alzahrani
et al.

Abstract: Background Herpes zoster (shingles) is caused by reactivation of the varicella-zoster virus. Despite the recommended herpes zoster vaccine for individuals aged ≥ 50 years, its uptake remains low in Saudi Arabia. Methods This cross-sectional study assessed knowledge and awareness of herpes zoster and its vaccine in individuals aged ≥ 50 years in Saudi Arabia. Data were collected through an online survey distributed via social media. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
3
3
1
Order By: Relevance
“…Similarly, just under 30% were aware that the vaccine is also indicated for those 18 years or older with a history of autoimmune disease or who are on immunosuppressive medication. Our finding is in line with other research indicating a general lack of knowledge about vaccine indications among the public [ 12 , 15 , 17 ]. This gap in knowledge may be attributed to the absence of campaigns related to HZ and its vaccination.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similarly, just under 30% were aware that the vaccine is also indicated for those 18 years or older with a history of autoimmune disease or who are on immunosuppressive medication. Our finding is in line with other research indicating a general lack of knowledge about vaccine indications among the public [ 12 , 15 , 17 ]. This gap in knowledge may be attributed to the absence of campaigns related to HZ and its vaccination.…”
Section: Discussionsupporting
confidence: 93%
“…A few studies have suggested a limited awareness of HZ and its vaccination among the Saudi population. However, the magnitude is unknown [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the vaccination rate (8%) was lower than expected. This aligns with a small percentage of individuals who had already been vaccinated, consistent with a previous study conducted in Saudi Arabia [ 9 ]. This similarity may be attributed to factors such as accessibility or vaccine availability in both study populations.…”
Section: Discussionsupporting
confidence: 92%
“…The results indicated that a majority of the participants had heard of herpes zoster, albeit less than reported in a previous study conducted in Saudi Arabia [ 9 ]. In terms of the acceptance of the herpes zoster vaccine, a high percentage believed the VZV vaccine to be effective (89%) and available in Saudi Arabia (87%).…”
Section: Discussioncontrasting
confidence: 63%
“…The Italian Ministry of Health does not currently provide vaccination coverage rates for Herpes Zoster but merely indicates an optimal coverage of 50% [ 22 ]. Recent international studies have reported varied uptake rates, ranging from approximately 8% in Saudi Arabia to 46.9% in Australia, with a similar uptake observed in Greece (12%) [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%